The Significance of the Title in the Play The Killers “A Semiotic Study” (Al-Farooq Journal of Sciences, 2026)
It is clear from the above that the title is closely connected to the body of the text. It does not represent merely passing words or a formal expression; rather, it is an important semantic element that summarizes the content of the work and prepares the reader to enter the world of the text. The internal titles also came as complementary and explanatory elements to the original title, as they were arranged according to a chronological sequence that reflects the development of events and helps the reader understand the meaning the writer intended to convey.The writer drew inspiration for his play from a television drama entitled “The Execution Platform” by Dr. Raouf Saad, which itself is derived from The Tale of the Hunchback in One Thousand and One Nights. Therefore, the title of the play “The Killers” came loaded with symbolic, suggestive, and descriptive meanings. Its selection was not random; rather, it was consistent with the content of the text, its events, and its characters.The secondary titles also contributed to removing part of the ambiguity surrounding the main title, as they revealed the stages of the event in a gradual and organized manner without separating from the general structure of the text. Through this, it becomes clear that the original title, together with the iconic image, color, and genre title, formed an integrated semantic unit that provided the reader with initial indications about the content of the play and guided him toward a deeper understanding of its artistic and thematic dimensions.